Teachers' and Parents' Attitudes Towards the Motives for Privatizing Education in Arab Private Schools in the Haifa and Upper Galilee Areas - Khalaily, Lubna Ali Elenat (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the attitudes of teachers and parents towards the motives of privatizing education in Arab private schools in the Haifa and Upper Galilee area. To achieve the study objectives, the researcher used the descriptive analytical approach and the questionnaire as a tool for collecting data. After verifying its validity and reliability, it was applied to the study sample of teachers and parents, numbering (304) teachers and (629) parents in the academic year (2022-2021). They were reached using the stratified random cluster method.The results of the study showed that the attitudes of teachers and parents towards the motives of privatizing Arab education in the Haifa and Upper Galilee area were high, with an arithmetic mean of (3.71). The results also showed that there were no statistically significant differences at the significance level (α≤ 0.05) between the estimates of the study sample averages attributed to the study variables, which are: the status characteristic, educational level, monthly family income. Based on the results, the study recommended the necessity of developing new policies that support public education, and allocating budgets for private and public education in order to improve the educational and pedagogical process.
Keywords: Trends; teachers and family; motives; privatization of education